3
$\begingroup$

Let $a$, $b$ and $c$ be positive numbers such that $a+b+c=2$. Prove: $$\frac{ab}{\sqrt{2c+a+b}}+\frac{bc}{\sqrt{2a+b+c}}+\frac{ca}{\sqrt{2b+c+a}}\le\sqrt\frac{2}{3}$$

Additional info:I'm looking for solutions and hint that using Cauchy-Schwarz, Hölder and AM-GM because I have background in them.

Things I have tried: I was thinking to making the denominator smaller using AM-GM.but I was not successful. My other idea was to re write LHS into this form.something like my idea on this question $$A-\frac{ab}{\sqrt{2c+a+b}}+B-\frac{bc}{\sqrt{2a+b+c}}+C-\frac{ca}{\sqrt{2b+c+a}}$$

But I was not able to observe something good.

I don't know this will lead to something useful but,here is my other idea. let $x=2c+a+b,y=2a+b+c,z=2b+c+a$. rewriting LHS:$$\sum\limits_{cyc}\frac{(3y-(x+z))(3z-(y+x))}{16\sqrt x} \le \sqrt\frac{2}{3}$$ $\sum\limits_{cyc}$denotes sums over cyclic permutations of the symbols $x,y,z$ . another thing I observed that $(x-y-z)^2-4(y-z)^2 = (3y-(x+z))(3z-(y+x))$

I looked at related problems and I think this and (Prove $\frac{a}{ab+2c}+\frac{b}{bc+2a}+\frac{c}{ca+2b} \ge \frac 98$) may have some common idea in proof with my question inequality.

Well,it seems like someone posted it a little after on AoPS.right now there is a solution there by $uvw$ and Cauchy-Schwarz. I post the starting part of solution that is with Cauchy (credits to arqady of AoPS). By Cauchy-Schwarz:$$\left(\sum_{cyc}\frac{ab}{\sqrt{2c+a+b}}\right)^2\leq(ab+ac+bc)\sum_{cyc}\frac{ab}{2c+a+b}$$

Hence, it remains to prove that: $$(ab+ac+bc)\sum_{cyc}\frac{ab}{2c+a+b}\leq\frac{(a+b+c)^3}{12}$$

I stuck here.

$\endgroup$
6
$\begingroup$

Well I think figured out . I will write it down from first.

By Cauchy-Schwarz: $$\left(\sum_{cyc}\frac{ab}{\sqrt{2c+a+b}}\right)^2\leq(ab+ac+bc)\sum_{cyc}\frac{ab}{2c+a+b}$$

Hence, it remains to prove that: $$(ab+ac+bc)\sum_{cyc}\frac{ab}{2c+a+b}\leq\frac{(a+b+c)^3}{12}$$

by the well known inequality:$$3(ab+bc+ca)\le(a+b+c)^2$$

So $$(ab+bc+ca)\le\frac{(a+b+c)^2}{3}$$

is true.it remain to show that $$\sum_{cyc}\frac{ab}{2c+a+b}\le \frac{(a+b+c)}{4}=\frac{1}{2}$$

by well known inequality $$\frac{1}{x}+\frac{1}{y}\ge\frac{4}{x+y}$$

So $$\frac{ab}{c+a}+\frac{ab}{c+b}\ge\frac{4ab}{2c+a+b} \rightarrow \frac{1}{4}(\frac{ab}{c+a}+\frac{ab}{c+b}) \ge\frac{ab}{2c+a+b} $$

so we can conclude that $$\frac{1}{4}\sum\limits_{cyc}(\frac{ab}{c+a}+\frac{ab}{c+b})=\frac{1}{4}(a+b+c)=\frac{1}{2}\ge\sum_{cyc}\frac{ab}{2c+a+b}$$

Done.

$\endgroup$
0
$\begingroup$

By AM-GM and C-S we obtain: $$\sum_{cyc}\frac{ab}{\sqrt{2c+a+b}}=\sum_{cyc}\frac{ab\sqrt{\frac{3}{8}}\cdot2\sqrt{\frac{8}{3}(2c+a+b)}}{2(2c+a+b)}\leq\sqrt{\frac{3}{32}}\sum_{cyc}\frac{ab\left(\frac{8}{3}+2c+a+b\right)}{2c+a+b}=$$ $$=\sqrt{\frac{1}{96}}\sum_{cyc}\frac{ab(4(a+b+c)+6c+3a+3b)}{2c+a+b}=\sqrt{\frac{1}{96}}\sum_{cyc}\frac{ab(10c+7a+7b)}{2c+a+b}=$$ $$=\sqrt{\frac{1}{96}}\sum_{cyc}\left(\frac{-4abc}{2c+a+b}+7ab\right)\leq\sqrt{\frac{1}{96}}\left(\frac{-36abc}{\sum\limits_{cyc}(2c+a+b)}+7(ab+ac+bc)\right)=$$ $$=\sqrt{\frac{1}{96}}\left(\frac{-9abc}{a+b+c}+7(ab+ac+bc)\right).$$ Thus, it remains to prove that $$\sqrt{\frac{1}{96}}\left(\frac{-9abc}{a+b+c}+7(ab+ac+bc)\right)\leq\sqrt{\frac{2}{3}}$$ or $$\frac{-9abc}{a+b+c}+7(ab+ac+bc)\leq8$$ or $$\frac{-9abc}{a+b+c}+7(ab+ac+bc)\leq2(a+b+c)^2$$ or $$\sum_{cyc}(2a^3-a^2b-a^2c)\geq0$$ or $$\sum_{cyc}(a-b)^2(a+b)\geq0.$$ Done!

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.